A comparative analysis testing Werner's theory of complex life cycles. (24th May 2022) - Richardson, Emily L.; White, Craig R.; Marshall, Dustin J.
Abstract: A popular theoretical model for explaining the evolution of complex life cycles (CLCs) was provided by Earl Werner. The theory predicts the size at which an individual should switch stages to maximise growth rate relative to mortality rate across the life history. Werner's theory assumes that body size does not change during the transition from one phase to another (e.g. from larva to adult)—a key assumption that has not been tested systematically but could alter the predictions of the model. We quantified how growth rate and mass change across larval stages and metamorphosis for 105 species of fish, amphibians, insects, crustaceans and molluscs. Across all taxonomic groups, we found support for Werner's assumption that growth rates are maintained or increase around transitions. We found that changes in growth and mass were greatest during metamorphosis, and change in growth correlated with development time. Importantly, most species either gained or lost mass when switching to a new stage—a direct contradiction of Werner's assumption. When we explored the consequences of energy loss and gain in a numerical model, we found that individuals should switch stages at a larger and smaller size, respectively, relative to what Werner's standard theory predicts. Our results suggest that while there is support for Werner's assumption regarding growth rates, mass changes profoundly alter the timing of transitions that are predicted to maximise fitness, and therefore the original model omits an important component that may contribute to the evolution of CLCs. Future studies should test for conditions that alter the costs of transitions, so that we can have a better understanding of how mass loss or gain affects fitness. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.